A 2233-year tree-ring chronology of subarctic black spruce (Picea mariana): growth forms response to long-term climate change. Issue 3 (2nd October 2021) - Delwaide, Ann; Asselin, Hugo; Arseneault, Dominique; Lavoie, Claude; Payette, Serge
ABSTRACT: We present the longest tree-ring chronology to date in northeastern North America (2233 years; 227 BCE – 2005 CE), resulting from several research projects conducted at the subarctic treeline in northern Quebec. This raw chronology of tree-ring width includes 464 black spruce ( Picea mariana (Mill.) B.S.P.) shrubs (krummholz) growing in wetlands and preserved within peatlands. An indexed series of 152 erect black spruce trees that have lived in wetlands is also presented, covering the period 216 BCE to 1619 CE. We compared these chronologies to a tree-ring series including 116 black spruce trees and krummholz having grown on well-drained lichen woodlands over the period 1304–2000 CE. These chronologies highlight the major climatic periods of the last two millennia. Floating chronologies dating from 2500 to 3500 years ago were also developed from trees preserved in frozen peat. Growth rings from this period are much wider than those of the last 2233 years, suggesting warm climatic conditions and permafrost-free peatlands during the transition from mid- to late Holocene. The three subarctic chronologies presented here underscore the relevance and usefulness of tree growth rings and growth forms as ecological tools to assess the influence of climate on subarctic ecosystems.